2012
DOI: 10.1002/ab.21450
|View full text |Cite
|
Sign up to set email alerts
|

Students Aggress Against Professors in Reaction to Receiving Poor Grades: An Effect Moderated by Student Narcissism and Self‐Esteem

Abstract: Laboratory evidence about whether students' evaluations of teaching (SETs) are valid is lacking. Results from three (3) independent studies strongly confirm that "professors" who were generous with their grades were rewarded for their favor with higher SETs, while professors who were frugal were punished with lower SETs (Study 1, d = 1.51; Study 2, d = 1.59; Study 3, partial η(2) = .26). This result was found even when the feedback was manipulated to be more or less insulting (Study 3). Consistent with laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 58 publications
(108 reference statements)
1
15
1
1
Order By: Relevance
“…Their intrapersonal strategies (e.g., externalizing blame, distorting past events; Campbell et al, ; Foster & Campbell, ) are not necessarily unfavorable and might in fact be beneficial for their psychological health and well‐being because they can help buffer the negative effects of such threats (Sedikides et al, ). However, their primary behavioral strategy seems to be aggression or derogation against the source of threat (Barry et al, ; Bushman & Baumeister, ; Thomaes, Bushman, Orobio de Castro, Cohen, & Denissen, ; Vaillancourt, ), which has negative implications for their personal as well as professional relationships (Back et al, ). Contrary to prior research, which studied aggression as narcissists’ predominant behavioral response to ego threats, we proposed that, when given the opportunity, narcissists could utilize a more constructive behavioral strategy and attempt to counter ego threat via improved performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their intrapersonal strategies (e.g., externalizing blame, distorting past events; Campbell et al, ; Foster & Campbell, ) are not necessarily unfavorable and might in fact be beneficial for their psychological health and well‐being because they can help buffer the negative effects of such threats (Sedikides et al, ). However, their primary behavioral strategy seems to be aggression or derogation against the source of threat (Barry et al, ; Bushman & Baumeister, ; Thomaes, Bushman, Orobio de Castro, Cohen, & Denissen, ; Vaillancourt, ), which has negative implications for their personal as well as professional relationships (Back et al, ). Contrary to prior research, which studied aggression as narcissists’ predominant behavioral response to ego threats, we proposed that, when given the opportunity, narcissists could utilize a more constructive behavioral strategy and attempt to counter ego threat via improved performance.…”
Section: Discussionmentioning
confidence: 99%
“…However, their dominant interpersonal defense strategies include reestablishing dominance and eliminating the source of the threat (Baumeister, Smart, & Boden, ). Indeed, prior research has consistently shown that narcissists respond aggressively to ego threats such as negative feedback or rejection (Leary, Terry, Allen, & Tate, )—both physically and more covertly via derogating the evaluator (Barry, Chaplin, & Grafeman, ; Bushman & Baumeister, ; Twenge & Campbell, ; Vaillancourt, ).…”
Section: Overview Of the Studiesmentioning
confidence: 99%
“…This context should be taken into account in future study. In a most recent study in a sample of Canadian college students, Vaillancourt (2013) found that students rated their professors low in reaction to receiving poor grades in students' evaluation of teaching. Although our study showed that evaluations conducted at the beginning of the spring semester produced better evaluation results, we did not know if this was somewhat also the case in our Chinese student sample (e.g., whether students rated their teachers low in reaction to receiving poor grades in the final exams last semester).…”
Section: Limitationsmentioning
confidence: 99%
“…Perilaku agresif memiliki hubungan positif terhadap masalah-masalah psikologis lainnya yakni gangguan kepribadian narsistik (Ojanen, et al, 2012;Vaillancourt, 2013;Ghim, et al, 2015, Fitriyah & Purwoko, 2018, kenakalan remaja dan depresi (Tucker, et al, 2014), depresi (Blain-Arcaro, 2016), kecemburuan (Wright, 2014), rendahnya empati (van Hazebroek, 2016), selfcontrol yang rendah (Morsunmbul, 2015;Guo, et al, 2016), self-injury (Tang, et al, 2013), self-perception (Wallance et al , 2012), depresi dan stress (Esteves, 2018). Banyaknya masalah psikologis yang erat dengan perilaku agresif merupakan sinyal bahwa perilaku agresif merupakan masalah utama yang berdampak sistemik pada kondisi psikologis manusia.…”
Section: Pendahuluanunclassified